PENGARUH STRUKTUR MODAL DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN : (Studi Kasus Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2023) - Wiyono, Pazrin; Rasjid, Herlina; Machmud, Rizan (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study seeks to assess the impact of capital structure and dividend policy on the valuation of mining firms listed on the Indonesia Stock Exchange from 2019 to 2023. This study employs the Debt to Asset Ratio (DAR) and Dividend Payout Ratio (DPR) as independent variables, while Price to Book Value (PBV) functions as the dependent variable. The study population included 81 companies, but the sample size encompassed 14 companies.Methods: The analytical technique utilized was multiple linear regression, performed with SPSS software version 24. The research employed the Purposive Sampling technique, leading to the observation of 14 organizations.Results: The research results revealed that capital structure (DAR) significantly influences firm value, while dividend policy (DPR) does not. However, both variables simultaneously influence firm value. This finding indicates that optimal capital structure management is crucial for increasing firm value, while dividend policy requires an effective strategy in operational and financial management to drive improved performance and profitability. Keywords: Capital Structure, Dividend Policy, Firm Value